The pragmatic particles baš and upravo, тъкмо and именно (exactly and namely) in Croatian and Bulgarian - Stefčeva, Rosica (ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023., 2026)
The study offers a model for describing the pragmatic particles baš and upravo, тъкмо and именно (exactly and namely) in the Croatian and Bulgarian languages. The leading method is holistic and based on Yu. Apresyan’s theory of integral description of language, and it integrates the Rhetorical Structure Theory and the Relevance Theory. The integral description model endeavors to establish a correlation between the structural linguistic and discursive pragmatic characteristics of the particles. With the help of analytical interpretation of dictionary definitions, there is constructed a model of management of the particles on an in-depth syntactic level. The analysis of examples from the national corpora aims to show how the discursive properties of the particles are determined by their management model and its variance under the influence of context. The analyzed particles signal primarily rhetorical relations of an explicative type ‒ detailing and rephrasing, which render communication more effective and meaningful.